Toward an Efficient Data Dissemination Protocol for Vehicular Ad-Hoc Networks - Guidoni, Daniel L.; Gottsfritz, Euclydes N. [UNESP]; Meneguette, Rodolfo I.; Silva, Cristiano M.; Filho, Geraldo P. Rocha; Souza, Fernanda Sumika H. (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Data Dissemination protocols are used for several vehicular applications, varying from warning messages to real-time video delivery. The majority of literature solutions consider the distance from the sender to choose the vehicle to forward the message. Basically, the solutions introduce a delay in the forwarding procedure, which is inversely proportional to the distance from the sender vehicle. In order to improve the forwarding procedure, this work introduces the concept of Road Covered Area to improve the overall data dissemination process and we describe how to calculate the road covered area by a node transmission. We present the D&RCA, the combination of Distance and Road Covered Area strategies to enhance the re-transmission during communication. Instead of considering the distance, we propose a function to combine the distance and road covered area to introduce a small delay before re-transmissions. We compare the proposed protocol with literature solutions considering the metrics of number of collisions, network coverage and communication latency for different density of vehicles in the network. When the network has 700 vehicles/km2, the data dissemination latency and number of collisions of the proposed D&RCA is, respectively, 1.24 and 1.32 times smaller than the literature solutions. When we increase the density of vehicles, all evaluated solutions present a network coverage above 90%.
Keywords: Communication protocol; data dissemination; road covered area; vehicular ad hoc network